2013
DOI: 10.3109/02688697.2013.841854
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of therapeutic effects between selective amygdalohippocampectomy and anterior temporal lobectomy for the treatment of temporal lobe epilepsy: A meta-analysis

Abstract: It is advised that clinically, physicians should choose the appropriate approach according to operation indications to improve the results of postoperative recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 22 publications
2
29
0
1
Order By: Relevance
“…Previous studies have revealed that most lesional TLE patients exhibited a very favorable prognosis after ATL or SAH [36][37][38].Clinically, although the semiology and EEG results indicate a temporal epileptic focus in patients, currently MRI studies may fail to detect any lesions. MRI-negative TLE is considered one of the main factors that predicts poor seizure outcome due to the technical difficulties involved in localizing and resecting the entire epileptogenic focus [2,3,8].…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have revealed that most lesional TLE patients exhibited a very favorable prognosis after ATL or SAH [36][37][38].Clinically, although the semiology and EEG results indicate a temporal epileptic focus in patients, currently MRI studies may fail to detect any lesions. MRI-negative TLE is considered one of the main factors that predicts poor seizure outcome due to the technical difficulties involved in localizing and resecting the entire epileptogenic focus [2,3,8].…”
Section: Discussionmentioning
confidence: 94%
“…The choice of resective surgery for TLE remains elusive. Previous meta-analyses have shown discordant findings, with ATL reported to achieve better seizure outcome when compared with SAH in two meta-analyses,4 5 and similar seizure outcome was reported with ATL and SAH in another meta-analysis 6. Hu et al 4 also showed that there was no significant difference in full-scale performance and verbal IQ scores of ATL relative to SAH.…”
Section: Introductionmentioning
confidence: 90%
“…Along these lines of reasoning, limited ablations should be preferred over more generous approaches [36]. However, some authors have found improved seizure control and worse neuropsychological outcome after larger resections [37], while others did not find any statistically significant difference between larger and more restricted procedures concerning seizure and neuropsychological outcome [38]. …”
Section: Discussionmentioning
confidence: 99%